Kinematics and geometry of structures in the southern limb of the Paraíba do Sul divergent structural fan, SE Brazil: a true transtensional shear - Dehler,Nolan M. (2006)
Shear zones geometry in the Paraíba do Sul belt, southeastern Brazil, delineates a NE-trending fan-like structure. Shear zones dip towards SE in the northern limb, and towards NW in the southern one. This geometry has been interpreted either due to transpression or to late folding of flat-lying thrust surfaces. Stretching lineation plunges to ENE-ESE in the northern limb and towards NNE-NE in the southern one. Structural data in the southern limb of the divergent fan suggest a two stage kinematic evolution in high-temperature conditions: an earlier stage with top-to-SSW/SW sinistral thrusting and orogenic-parallel tangential motion, and a later stage with top-down to NNE/NE transtensional deformation. We propose a heterogeneous deformation model to explain the observed shear reversal, and suggest that the imposed transpressional displacement gradient may change during progressive deformation due to transient rheological inhomogeneities in bulk pure shear strain. In the earlier stage, the partially molten material could easily accommodate the imposed strain rates, giving rise firstly to the SW-directed shearing. As the thermal disturbance tended to vanish and the convergence increased, the NNE-directed transtensional shearing developed. We propose that the transtensional deformation characterized in this paper could be related to extrusion processes during regional transpressional strain.